Vers une meilleure compréhension de la contribution des services sociaux à l’insertion sociale de jeunes adultes en difficulté - Marie-Ève Turcotte; Céline Bellot (Sociétés et Jeunesses en Difficulté)
While an extension of the period defining youth occurred in the last decades, and considering that young people now depend on their parents longer, transitioning to adulthood seems much more difficult for young people leaving care when compared to other youths, because they often lack positive support from family and friends. These youth, who often have difficulty to integrate themselves socially, tend not to ask for professional help in times of need. Within the framework of this qualitative study, which took place in Laval (Quebec) in 2007, ten young adults emancipated from the care system were interviewed. The objectives of the study were to clarify their social integration trajectories and their relationships with the social services network, and to assess the social services’ contribution to their social integration processes. Results tend to indicate that, unlike what some studies may suggest, most young adults who have formerly been placed in a substitute care setting are not heading for social exclusion as they enter adulthood. Besides, it appears that youths’ social integration strategies may vary according to gender. Thus, compared to young women, young men who participated in this study tend to rely less on social services professionals in order to move towards social integration. However, these results are not to be generalized to other populations and have to be interpretated with precaution, considering among other things the small number of youth who participated in this study (n=10).